Pemberian Diet Tambahan pada Anak dengan Penyakit Jantung Bawaan Asianotik - M. Wishnuwardhana; M. Mexitalia; JC. Susanto (MEDIA MEDIKA INDONESIANA, 2009)
Food supplementation for children with acyanotic congenital heart diseaseBackground: Children with Congenital Heart Disease (CHD) have a high risk for growth faltering. The prevalence of undernutrition in children with acyanotic CHD on the Pediatric Cardiology Clinic Dr. Kariadi Hospital Semarang is 80.4%. The purpose of the study is to define the benefit of food supplementation to children with acyanotic CHD to improve their growth.Methods: Clinical trial with one group pre and post test design study were conducted in children with CHD in the Pediatric Cardiology Clinic Dr. Kariadi Hospital Semarang during 2005-2006. Twenty-two children aged 6-57 months were involved in this study. Besides their daily intake, they had been given biscuit as food supplementation for 3 months, 20% above their Requirement Daily Allowance (RDA). Their weight and length/height were measured every months. The data was analyzed using Wilcoxon test.Results: The mean of Weight of Age z score (WAZ), Height of Age z score (HAZ), and Weight of Height z score (WHZ) before the supplementation were -1.570.9; -0.751.97; and -0.891.7 respectively. After 3 months there were an increased on WAZ 0.16 and HAZ 0.33 significantly but the improvement of WHZ is 0.01 (not significant). During the supplementation the calorie and protein intake were increased 14.6% and 8.4% respectively.Conclusion: Food supplementation with biscuit 14.6% above the RDA for 3 months improve the growth of children with acyanotic CHD.Keywords: Food supplementation, growth, acyanotic CHDABSTRAKLatar belakang: Anak dengan penyakit jantung bawaan (PJB) merupakan anak yang rawan mengalami gangguan pertumbuhan. Di Klinik Kardiologi Anak RSUP Dr. Kariadi Semarang, didapatkan 80,4% anak dengan PJB asianotik mengalami gizi kurang. Pemberian diet tambahan diharapkan memperbaiki status gizi dan pertumbuhan. Tujuan penelitian ini untuk mengetahui manfaat diet tambahan pada anak dengan PJB asianotik terhadap pertumbuhan.Metode: Uji klinis one group dengan pre and post test design, dilakukan pada anak dengan PJB asianotik di Klinik Kardiologi Anak RSUP Dr. Kariadi Semarang tahun 2005-2006. Dua puluh dua anak berumur 6-57 bulan diberikan perlakuan dengan pemberian biskuit sampai dengan 20% di atas Angka Kecukupan Gizi (AKG) selama 3 bulan selain tetap diberikan diet sehari-hari. Setiap bulan berat badan, panjang/tinggi badan diukur. Data dianalisis dengan uji Wilcoxon dengan batas kemaknaan p<0,05.Hasil: Sebelum perlakuan rerata z skor BB/U (WAZ) -1,570,9, z skor TB/U (HAZ) -0,751,97, z skor BB/TB (WHZ) rerata -0,891,7 dan sesudah perlakuan WAZ BB/U -1,411, HAZ -0,421,8, WHZ -0,881,6. Peningkatan rerata pertumbuhan sebelum dan sesudah perlakuan WAZ 0,16, HAZ 0,33 dan WHZ 0,01. Didapatkan perbedaan bermakna pada WAZ dan HAZ sedangkan WHZ tidak bermakna. Akseptabilitas meningkat setiap bulan dan terjadi peningkatan bermakna rerata asupan energi dan protein yang bersumber dari biskuit masing-masing sebesar 14,6% dan 8,4% dalam waktu 3 bulan.Simpulan: Pemberian biskuit minimal 14,6% di atas AKG selama 3 bulan pada anak PJB asianotik meningkatkan pertumbuhan.